2021
DOI: 10.7150/ijbs.60114
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the important roles of tumor cell-intrinsic PD-1

Abstract: PD-1 (Programmed cell death protein-1) is mainly expressed in various immune cells, while its ligands PD-L1/PD-L2 (Programmed death ligand-1/Programmed death ligand-2) are mostly expressed in tumor cells. Generally, the binding of PD-L1/PD-L2 and PD-1 could lead to the tumor immune evasion. However, some recent studies showed that PD-1 could also be expressed in tumor cells and could activate mTOR (Mammalian Target of Rapamycin) or Hippo signaling pathway, therefore facilitating tumor proliferation independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…The results shown that the PD-1 was high expression for pan-CK − cells in AAH/AIA stage, while inversely PD-1 was high expression for pan-CK + cells in MIA an IA stages. This is in line with a similar study showing that PD-1 could be expressed in tumor cells and could activate mTOR or Hippo signaling pathway, therefore facilitating tumor proliferation 59 . Taken together, interactions related to immunomodulatory signaling were more abundant in LUAD in comparison with normal, indicating heterogeneity and plasticity of the tumor ecosystem, varying during cancer progression.…”
Section: Resultssupporting
confidence: 91%
“…The results shown that the PD-1 was high expression for pan-CK − cells in AAH/AIA stage, while inversely PD-1 was high expression for pan-CK + cells in MIA an IA stages. This is in line with a similar study showing that PD-1 could be expressed in tumor cells and could activate mTOR or Hippo signaling pathway, therefore facilitating tumor proliferation 59 . Taken together, interactions related to immunomodulatory signaling were more abundant in LUAD in comparison with normal, indicating heterogeneity and plasticity of the tumor ecosystem, varying during cancer progression.…”
Section: Resultssupporting
confidence: 91%
“…The discovery of tumor immune escape mechanisms promotes the development of immune checkpoint inhibitors (ICIs) [ 4 ]. However, non-sensitivity and adverse reactions to ICIs limited their practical application [ 5 , 6 ]. Therefore, there is a need to elucidate the mechanisms of cancer pathogenesis to predict and increase the sensitivity of ICIs for tumor patients.…”
Section: Introductionmentioning
confidence: 99%
“…PD-1 inhibited the autoimmune response by binding PD-L1 or PD-L2 and inhibiting the function of T lymphocytes. Both PD-1 and PD-L1 have been found to be expressed in tumor cells, and the PD-1/PD-L2 axis has been shown to inhibit tumor growth via the AKT and ERK1/2 pathways [ 43 ]. CTLA-4 acted as a transmembrane receptor on T cells that bound to receptors on the surface of antigen cells to terminate the immune response [ 44 ].…”
Section: Discussionmentioning
confidence: 99%